1978
DOI: 10.1002/1097-0142(197808)42:2<512::aid-cncr2820420220>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal dysgenesis with adenocarcinoma of the endometrium.An electron microscopic and steroid receptor analyses with a review of the literature

Abstract: A patient with gonadal dysgenesis who developed endometrial carcinoma in her 31st year of estrogen therapy is discussed in relation to thirteen previously reported cases of carcinoma of the uterus in patients with Turner's syndrome. The pattern of steroid receptor proteins in the endometrial carcinoma was found to correlate with the degree of differentiation of the tumor as assessed by light and electron microscopy. The findings reflect a potential for continued hormonal responsiveness of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…affect gonadal function, and there are also raised prevalence rates of various other abnormalities, for instance cardiovascular and urinary tract abnormalities in Turner's syndrome and mental retardation in patients with additional sex chromosomes. Raised cancer risks have been reported in association with particular sex chromosome abnormalities -breast cancer (Scheike et al 1973) and mediastinal teratoma (Nichols et al 1987 ;Hasle et al 1992Hasle et al , 1995 in men with Klinefelter's syndrome, gonadal (ovarian) cancer in women with Turner's syndrome with Y chromosome material present (Krasna et al 1992), and endometrial cancer in relation to oestrogen treatment of Turner's syndrome (McCarty et al 1978 ;Clement & Young, 1987). There have also been case-reports suggesting the possibility of raised risks of many other cancers.…”
mentioning
confidence: 99%
“…affect gonadal function, and there are also raised prevalence rates of various other abnormalities, for instance cardiovascular and urinary tract abnormalities in Turner's syndrome and mental retardation in patients with additional sex chromosomes. Raised cancer risks have been reported in association with particular sex chromosome abnormalities -breast cancer (Scheike et al 1973) and mediastinal teratoma (Nichols et al 1987 ;Hasle et al 1992Hasle et al , 1995 in men with Klinefelter's syndrome, gonadal (ovarian) cancer in women with Turner's syndrome with Y chromosome material present (Krasna et al 1992), and endometrial cancer in relation to oestrogen treatment of Turner's syndrome (McCarty et al 1978 ;Clement & Young, 1987). There have also been case-reports suggesting the possibility of raised risks of many other cancers.…”
mentioning
confidence: 99%
“…22 Instead, the occurrence of sarcomas in Turner's syndrome is a very rare event with only few published cases. [4][5][6][7][8][9] For the endometrial sarcomas, as already postulated for endometrial carcinomas, 23,24 it has been suggested that the risk may be increased by estrogen replacement therapy or endogenous disorders that lead to unopposed estrogenic stimulation of the uterus. 6,7 This mechanism has also been recalled for LMS of the uterus 25 and oral cavity 26 of patients without Turner's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term estrogen administration to these patients or in individuals with other forms of GD represents a risk factor for endometrial carcinoma [60].…”
Section: Patients With Chromosomal Mosaicismmentioning
confidence: 99%